Screening and efficacy evaluation of antagonistic fungi against Phytophthora infestans and combination with arbuscular mycorrhizal fungi for biocontrol of late blight in potato - Lalaymia, Ismahen; Naveau, Françoise; Arguelles Arias, Anthony; Ongena, Marc; Picaud, Thierry; Declerck, Stéphane; Calonne-Salmon, Maryline (Frontiers in Agronomy, 2022)
Late blight caused by Phytophthora infestans is the most devastating disease of potato crops worldwide. Control practices mostly rely on synthetic fungicides or copper-based products. In the recent years, biological control agents have generated significant enthusiasm as eco-friendly sustainable alternatives. Here, the filtrates of 149 filamentous fungi and yeasts were tested in vitro against P. infestans MUCL 54981. The most effective filtrates were then combined in beads with the arbuscular mycorrhizal fungus (AMF) Rhizophagus irregularis MUCL 41833 and tested in vitro for their compatibility, and finally in the greenhouse for their efficacy against P. infestans. The filtrates of Penicillium aurantiogriseum MUCL 47586, Penicillium griseofulvum MUCL 29201, Trichoderma virens MUCL 18139 and Verticillium psalliotae MUCL 18310 totally suppressed conidial germination and growth of P. infestans in vitro. In whole potato plants in vitro, only the filtrate of T. virens significantly suppressed P. infestans plant infestation. With the exception of P. griseofulvum, none of the selected filtrates affected the germination, root colonization and spores production of R. irregularis following their combined entrapment in beads. According to these results, the filtrate of T. virens was selected for the greenhouse experiment with the potato variety Annabelle. The filtrate was used as leaf spray and/or as root treatment in combination with R. irregularis entrapped in alginate beads. Root treatments with AMF alone as well as with the AMF entrapped with the filtrate of T. virens significantly reduced the area under disease progress curves compared to the non-treated plants. LC-MS analyses of the filtrate showed the production of koninginin D, gliotoxin and koningic acid, three antifungal compounds, which could have impacted P. infestans. Conversely, foliar application of the filtrate, whether the plant was colonized by the AMF or not, did not reduce symptoms of the disease, possibly because of the greenhouse growth conditions making the potato plants more susceptible to P. infestans and counterbalancing the positive effects of the antimicrobial secondary metabolites or AMF. Our results demonstrated the potential of R. irregularis MUCL 41833 combined or not with a filtrate of T. virens MUCL 18139 into alginate beads as a biological control strategy against P. infestans.